2022
DOI: 10.1111/aspp.12628
|View full text |Cite
|
Sign up to set email alerts
|

More than just hedging? The reactions of Cambodia and Vietnam to the power struggle between the United States and China in times of Obama's “pivot to Asia”

Abstract: Southeast Asia is a major theater in the superpower rivalry between China and the United States. The states in this region face the challenge how to react to this intensified strategic competition. Some authors suggest a concept of hedging as the main behavioral response of the region. Nevertheless, critics argue that just one concept cannot incorporate all the variation in their behavior. They often name Cambodia and Vietnam as problematic examples -Cambodia rather bandwagoning with China and Vietnam being mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…On the other hand, Gerstl [1] conducts a qualitative study to examine both similarities and differences of hedging strategies of three Southeast Asian countries and one international organization towards a rising China. Furthermore, some case studies narrow down the criteria for comparison, as illustrated by the study that focuses on Cambodia's and Vietnam's hedging in the specific times of Obama's "pivot to Asia" policy [19] and the research that particularly taps into Southeast Asian countries' hedging response to the BRI [20].…”
Section: Comparative Studies Of Hedging Strategiesmentioning
confidence: 99%
“…On the other hand, Gerstl [1] conducts a qualitative study to examine both similarities and differences of hedging strategies of three Southeast Asian countries and one international organization towards a rising China. Furthermore, some case studies narrow down the criteria for comparison, as illustrated by the study that focuses on Cambodia's and Vietnam's hedging in the specific times of Obama's "pivot to Asia" policy [19] and the research that particularly taps into Southeast Asian countries' hedging response to the BRI [20].…”
Section: Comparative Studies Of Hedging Strategiesmentioning
confidence: 99%
“…So far, these predictions have not been borne out. Studies examining the foreign policy choices of ASEAN countries have demonstrated that most of these countries have adopted a third strategy: hedging, characterized by increased trade relations with China and robust security ties with the United States (Busbarat 2017;Heydarian 2017;Kuik 2016;Laksmana 2017;Murphy 2017;Noor and Qistina 2017;Syailendra 2017;Thayer 2017;Železný 2022). Moreover, there is little evidence that the deepening US-China competition will eliminate the space for the hedging strategy.…”
Section: Why Public Opinion About Hedging?mentioning
confidence: 99%
“…While this competition for allies and partners has been playing out all over the world, countries in Southeast Asia, all of whom are members of the Association of Southeast Asian Nations (ASEAN), have been under particular pressure to choose a side, as China's growing influence is most directly felt in its neighborhood. However, ASEAN countries have demonstrated considerable agency under the shadow of great-power competition, and a hedging strategy has emerged, whereby most nations in the region have remained equidistant between the two great powers, neither fully aligning with one to oppose the other, nor remaining too aloof to either (Busbarat 2017; Chan 2012; Ciorciari 2010; Heydarian 2017; Kuik 2016; Laksmana 2017; Murphy 2017; Noor and Qistina 2017; Syailendra 2017; Thayer 2017; Železný 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is hedging against China by forming strategic partnership with Japan. Meanwhile, some other scholars suggest that Cambodia used to hedging China, as seen in Phnom Penh supporting China-led Lancang-Mekong Cooperation (LMC) and US-led Lower Mekong Initiative (LMI) simultaneously, but has gradually shifted to bandwagoning in recent years (Doung et al, 2022;Železný, 2022).…”
mentioning
confidence: 99%